Faktor-faktor yang mempengaruhi minat mahasiswa akuntansi untuk berkarier di Kantor Akuntan Publik - Tyas, Nur Endah Wahyuning; Maryono, Maryono; Ali Ma’sum, Muhammad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine how much interest accounting students have for a career in public accounting firms. This research was conducted on accounting students who are still active at Stikubank University Semarang for the 2018-2020 period using convenience sampling with the availability of elements and the ease of obtaining them. The data used is primary data. The number of samples selected was 82 out of 478 accounting students who are still active at Stikubank University, Semarang. The data collection technique used is distributing online questionnaires with several question criteria. The results of this study indicate that gender; financial rewards; labor market considerations; professional recognition has a positive and significant effect on the interest of accounting students to have a career in public accounting firms.